Eating disorders in children and adolescents : a clinical handbook - Le Grange, Daniel; Lock, James (New York : Guilford Press, 2011)
'Eating disorders typically first appear during childhood and adolescence. Despite this early age of onset, edited volumes on eating disorders have not focused on this age cohort. One of the primary purposes of this book is to redress this imbalance and target the unique issues that pertain to the development, assessment, and treatment of eating disorders in children and adolescents, a period of heightened vulnerability to the these disorders and to the potential damage they can cause'--Provided by publisher.
culimia nervosa : theoretical model, key tenets, and evidence base / Daniel Le Grange -- ch. 16. Cognitive-behavioral therapy for adolescent bulimia nervosa and binge-eating disorder / Mari Campbell and Ulrike Schmidt -- ch. 17. Supportive psychotherapy for bulimia nervosa in adolescents / Renee Rienecke Hoste and Angela Celio doyle -- Other treatments or clinical groups -- ch. 18. Early treatment for eating disorders / Katharine L. Loeb . . . [et al.] -- ch. 19. Parent groups in the treatment of eating disorders / Nancy L. Zucker . . . [et al.] -- ch. 20. Treatments targeting aberrant eating patterns in overweight youth / Kerri N. Boutelle and Marian Tanofsky-Kraff -- ch. 21. Pharmacotherapy for eating disorders in children and adolescents / Jennifer Couturier and Wendy Spettigue -- Part VI. Prevention -- ch. 22. Prevention of eating disorders in children and adolescents / Dianne Neumark-Sztainer -- ch. 23. Innovative approaches to prevention and intervention : the Internet / Angela Celio Doyle, Roslyn Binford Hopf, and Debra L. Franko -- Part VII.The role of parents -- ch. 24. A parent's perspective on family treatment / Harriet Brown -- Concluding comments -- ch. 25. Where are we going from here? / James Lock.
Includes bibliographical references and indexes.
Keywords: Eating disorders in children; Eating disorders in adolescence